2021
DOI: 10.21873/anticanres.15411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diallyl Trisulfide on TNF-α-induced CCL2/MCP-1 Release in Genetically Different Triple-negative Breast Cancer Cells

Abstract: Background/Aim: Diallyl trisulfide (DATS) has been shown to prevent and inhibit breast carcinogenesis. CCL2/MCP-1 has been shown to play a significant role in breast cancer. This study explored DATS efficacy on triple-negative breast cancer (TNBC) cells. Materials and Methods: DATS efficacy on TNFα induced TNBC cells were examined via trypan blue exclusion test, wound-healing assay, human cytokine arrays, ELISA, and RT-PCR. Results: DATS significantly induced cell death and inhibited cell migration. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Another study explored the mechanism by which DADS attenuates TNF-α-induced CCL2 production and found that this compound inhibits TNF-α-induced CCL2 production primarily by reducing the expression of IKKε and pERK, impairing MAPK/ERK, and NFKB pathway signals [178] . Accordingly, the DADS mechanism of action is similar to TNF-inhibitors and influences CCL2 production by creating a disturbance in upstream signaling pathways involved in CCL2 expression [179] . Since anti-TNFs have been effective in reducing the severity of the disease in patients with COVID-19, perhaps these compounds can be used together with other CCL2/CCR2 inhibitors to make a synergistic therapeutic effect [180] .…”
Section: Therapeutic Approaches Based On Ccl2/ccr2 Axis Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study explored the mechanism by which DADS attenuates TNF-α-induced CCL2 production and found that this compound inhibits TNF-α-induced CCL2 production primarily by reducing the expression of IKKε and pERK, impairing MAPK/ERK, and NFKB pathway signals [178] . Accordingly, the DADS mechanism of action is similar to TNF-inhibitors and influences CCL2 production by creating a disturbance in upstream signaling pathways involved in CCL2 expression [179] . Since anti-TNFs have been effective in reducing the severity of the disease in patients with COVID-19, perhaps these compounds can be used together with other CCL2/CCR2 inhibitors to make a synergistic therapeutic effect [180] .…”
Section: Therapeutic Approaches Based On Ccl2/ccr2 Axis Targetingmentioning
confidence: 99%
“…Because of the critical role of CCR2 in the recruitment of inflammatory monocytes, the therapeutic potential of CCR2 antagonists for preventing and treating inflammatory, infectious, and autoimmune diseases has always been of interest to researchers. Although CCR2 antagonists could not succeed in clinical trials [179] , using CCR2 inhibitors achieved promising outcomes in cancer settings.…”
Section: Therapeutic Approaches Based On Ccl2/ccr2 Axis Targetingmentioning
confidence: 99%
“…Therefore, it is imperative to identify common biological markers for TNBC and plants that can be useful as both medicine and food in preventing breast cancer and its progression. Previously, we showed that DATS cytotoxicity was both dose- and time-dependent ( 44 ). DATS and TNF-α concentration was chosen based on the literature review as well as previous work done in our lab ( 9 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that DATS cytotoxicity was both dose- and time-dependent ( 44 ). DATS and TNF-α concentration was chosen based on the literature review as well as previous work done in our lab ( 9 , 44 ). In the present study, we demonstrated DATS ability to induce cell cycle arrest at the G 2 /M phase in genetically and ethnically different TNBC cells, specifically MDA-MB-231 and MDA-MB-468 cells, via flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has previously reported that the chemopreventive/chemotherapeutic potential of the garlic OSC, DATS, lies in its ability to induce apoptosis and cell cycle arrest in breast cancer cells and other cancers while attenuating S-phase cell cycle transition, suppressing ROS production and inhibiting DNA damage in breast epithelial (MCF-10A) cells [ 13 , 14 ]. Previous studies have demonstrated that DATS can induce apoptosis through oxidative modification and inhibition of ROS levels in human breast, colon, gastric, prostate, and bone cancer cell lines [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%